2020
DOI: 10.1155/2020/8859658
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of PVP Molecular Weight on Dissolution Behavior and Physicochemical Characterization of Glycyrrhetinic Acid Solid Dispersions

Abstract: The effect of polyvinylpyrrolidone (PVP) as glycyrrhetic acid (GA) solid dispersions carrier at different molecular weights on the dissolution behavior and physicochemical properties was investigated. PVP-GA-SDs prepared with all four molecular weight PVPs displayed good enhancement of dissolution rate and equilibrium solubility compared with pure drug and corresponding physical mixtures. The results showed that the enhancement effect of molecular weight on dissolution rate and equilibrium solubility follows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 42 publications
1
6
1
Order By: Relevance
“…In tablets prepared by the SSD technique using PVP, the significant decrease in the percentage of drug released upon increasing the polymer concentration to 5% was most likely owing to the elevated viscosity resulting from the high molecular mass of the polymer, in addition to the probable increased polymer chain entanglement which leads to slow motion of the drug molecules through the diffusion layer. These results, however, were in contrast to those obtained by Sui et al (2020) who found that the dissolution rate of glycyrrhetinic acid from its PVP solid dispersions with 8: 1 carrier-drug ratio was faster than 4: 1 under the same PVP molecular weight condition.…”
Section: In-vitro Drug Release Studiescontrasting
confidence: 99%
“…In tablets prepared by the SSD technique using PVP, the significant decrease in the percentage of drug released upon increasing the polymer concentration to 5% was most likely owing to the elevated viscosity resulting from the high molecular mass of the polymer, in addition to the probable increased polymer chain entanglement which leads to slow motion of the drug molecules through the diffusion layer. These results, however, were in contrast to those obtained by Sui et al (2020) who found that the dissolution rate of glycyrrhetinic acid from its PVP solid dispersions with 8: 1 carrier-drug ratio was faster than 4: 1 under the same PVP molecular weight condition.…”
Section: In-vitro Drug Release Studiescontrasting
confidence: 99%
“…PVP is well-known for being used as an ultrafast ES fibrous matrix to improve the solubility of BCS class II drugs such as FF [12,[32][33][34][35][36][37][38][39][40][41]. In this study, FF-PVP fibres showed the fastest drug release with over 50% drug release (t50) in under 2 minutes.…”
Section: Dissolution Of Freshly Prepared Ff-polymer Blend Es Fibresmentioning
confidence: 71%
“…Polyvinylpyrrolidone is characterized by its K-value [36], a function of the average molecular weight, the degree of polymerization and the intrinsic viscosity [37]. The viscosity was measured for aqueous PVP solutions [38] with K-values ranging from 92.1 to 95.4 and with concentrations from 2 to 3 weight percent. A correlation was determined that relates solution viscosity to the K value and weight percent PVP, which is particularly useful in its use as a photoresist in manufacturing high-resolution display screens [39].…”
Section: Choosing the Optimal Adhesive Formula For Use In Pharmaceuti...mentioning
confidence: 99%
“…The solvent had to meet the attributes mentioned above (inert, odourless, tasteless, frequently used) and slight evaporation. Although ideal for such use, water would result in high drying times [38]. Thus, isopropyl alcohol, ethyl alcohol and a stoichiometric mixture of them were chosen for the solvent.…”
Section: Choosing the Optimal Adhesive Formula For Use In Pharmaceuti...mentioning
confidence: 99%